Preparation method of micro / narrow mesoporous high-hydrophobicity biochar

By preparing micro/narrow mesoporous highly hydrophobic biochar, the problems of low efficiency and high cost of siloxane removal in biogas are solved, and efficient and environmentally friendly siloxane adsorption removal are achieved, demonstrating resource recycling and low cost Advantages of craftsmanship.

CN119303548APending Publication Date: 2025-01-14SHIJIAZHUANG UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411589713.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The prior art has problems such as high cost, complex operation, easy to produce secondary pollution and poor removal efficiency in removing siloxanes from biogas, making it difficult to achieve efficient, economical and environmentally friendly removal solutions.

Method used

The preparation method of micro/narrow mesoporous highly hydrophobic biochar is used to form biochar with micro/narrow mesoporous structure and high hydrophobicity through pretreatment of coconut bran raw materials, phosphoric acid impregnation, high temperature pyrolysis and surface hydrophobic modification. Used to efficiently adsorb and remove siloxane from biogas.

Benefits of technology

It realizes efficient adsorption and removal of silicones, reduces operating costs and environmental risks, has the advantages of large adsorption capacity, good selectivity, and easy regeneration, and reduces production costs through resource recycling. It is suitable for wastewater treatment, gas purification and other fields. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303548A_ABST
    Figure CN119303548A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adsorption materials, and provides a preparation method of micro / narrow mesoporous high-hydrophobicity biochar, which comprises the following steps: (1) cleaning coco coir with deionized water, drying, crushing and sieving to obtain particles with the particle size of 0.425 mm; mixing the particles in the step (1) with phosphoric acid in a mass ratio of 1: 3, stirring for 0.5 hour, putting the obtained mixture into a drying oven, and drying at 110 DEG C for 2 hours; (2) pushing the dried mixture into a heating zone of a tubular furnace under the condition that the flow rate of carbon dioxide is 100 ml / min, and keeping the temperature at 800 DEG C for 2 hours to obtain biochar BC; and (3) adding the BC in the step (2) into 0.25 wt% of an aqueous solution of methyltrimethoxysilane, oscillating at 25 DEG C for 12 hours, filtering, and carrying out vacuum drying on the obtained slurry at 120 DEG C for 24 hours to obtain the micro-narrow mesoporous high-hydrophobicity biochar. The waste coco coir is used as the raw material, the process is simple, the cost is low, the recovery efficiency is high (can reach 84.36%), and the method has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to a method for preparing micro / narrow mesoporous highly hydrophobic biochar for selectively adsorbing volatile methylsiloxane in biogas. Background Art

[0002] Biogas, as a renewable energy source, is mainly composed of methane, carbon dioxide and trace amounts of impurity gases. It is widely used in energy production, chemical raw materials and greenhouse gas emission reduction. However, in the production process of biogas, especially in the process of biomass fermentation or anaerobic digestion, siloxanes (such as dimethylsiloxane, trimethylsiloxane, etc.) are often generated. The presence of siloxanes will not only reduce the calorific value and combustion efficiency of biogas, but may also have an adverse effect on the operation of downstream equipment such as gas turbines and internal combustion engines, such as depositing silicides, clogging pipelines, and reducing heat exchange efficiency. Therefore, it is particularly important to effectively remove siloxanes from biogas.

[0003] At present, there are mainly the following technical methods for removing siloxanes from biogas:

[0004] (1) Adsorption method: Siloxane is physically adsorbed using adsorption materials such as biochar and molecular sieves. This method is simple to operate, but the adsorption capacity is limited, and as the adsorption saturation increases, the adsorbent needs to be replaced frequently, increasing the operating cost. In addition, the adsorption material may produce secondary pollution during the regeneration process.

[0005] (2) Chemical absorption method: alkaline solution (such as sodium hydroxide solution) is used to react chemically with siloxane to generate gas-insoluble sodium silicate and other substances, thereby achieving the removal of siloxane. However, this method has high requirements for equipment, and the waste liquid generated after the reaction needs to be properly handled to avoid pollution to the environment.

[0006] (3) Membrane separation method: Siloxane and other gas components are separated by selective permeability of specific membrane materials. This method has high separation efficiency, but the membrane material cost is high and it is easily contaminated and blocked, which affects long-term stable operation.

[0007] (4) Low temperature condensation method: By lowering the temperature of biogas, siloxane and other easily condensable components are condensed into liquid and separated. However, this method consumes a lot of energy and is not effective in removing low-concentration siloxane.

[0008] In summary, although the existing technologies have their own advantages in removing siloxane from biogas, they also have disadvantages such as high cost, complex operation, easy to generate secondary pollution or low removal efficiency. Therefore, developing an efficient, economical and environmentally friendly siloxane removal technology is of great significance to improving the quality of biogas and promoting the sustainable development of the biogas industry.

[0009] In this context, the present invention proposes a preparation method based on micro-narrow mesoporous high hydrophobic biochar, which aims to achieve efficient adsorption and removal of siloxanes in biogas by optimizing the pore structure and surface properties of biochar. This method not only has the advantages of large adsorption capacity, good selectivity, and easy regeneration, but also can effectively reduce operating costs and environmental risks, providing a new solution for the removal of siloxanes in biogas. Summary of the invention

[0010] In view of the above defects or deficiencies in the prior art, the present invention provides a method for preparing micro / narrow mesoporous highly hydrophobic biochar in order to solve the above problems in the prior art.

[0011] The main technical scheme is: a method for preparing micro / narrow mesoporous highly hydrophobic biochar, comprising the following steps:

[0012] (1) Raw material pretreatment: Coconut bran was selected as the raw material, and was first repeatedly washed with deionized water to remove impurities, and then dried to constant weight. The dried coconut bran was crushed and sieved through a 40-mesh sieve to obtain uniform particles with a particle size of about 0.425 mm.

[0013] (2) Phosphoric acid impregnation: The coconut husk particles obtained in step (1) were mixed with phosphoric acid and stirred at room temperature for 0.5 h to allow the phosphoric acid to fully penetrate into the coconut husk particles. The mixture was then transferred to an oven and dried at 110° C. for 2 h.

[0014] (3) High-temperature pyrolysis: The dried mixture in step (2) was placed in a tube furnace and subjected to high-temperature pyrolysis in a protective atmosphere with a carbon dioxide flow rate of 100 ml / min. The pyrolysis temperature was set to 800°C and maintained for 2 h, so that the coconut bran particles underwent carbonization reaction at high temperature to form biochar (BC) with a micro / narrow mesoporous structure.

[0015] (4) Surface hydrophobic modification: The BC obtained in step (3) was added to a methyltrimethoxysilane aqueous solution and shaken at 25°C for 12 hours to allow the methyltrimethoxysilane molecules to undergo hydrolysis and condensation reaction on the surface of the biochar and be grafted onto the surface of the biochar. Subsequently, the modified biochar was separated from the solution by filtration, and the obtained slurry was vacuum dried at 120°C for 24 hours to finally obtain a micro-narrow mesoporous highly hydrophobic biochar (MTMS@BC-0.25).

[0016] Furthermore, in the step (2), the mass ratio of coconut bran to phosphoric acid is 1:3.

[0017] Furthermore, in step (4), the mass fraction of the methyltrimethoxysilane aqueous solution is 0.25%.

[0018] Furthermore, in step (4), the mass ratio of BC to the methyltrimethoxysilane aqueous solution is 1:10.

[0019] The beneficial effects of the present invention are: (1) Structural optimization: The present invention successfully prepares biochar with micro / narrow mesoporous structures through a method combining phosphoric acid impregnation with high-temperature pyrolysis. These micro / narrow mesoporous structures help to improve the material's adsorption capacity for specific molecules. (2) High hydrophobicity: The introduction of methyltrimethoxysilane significantly improves the surface hydrophobicity of biochar, allowing it to maintain stable adsorption performance in a humid environment. (3) Environmental protection and high efficiency: Using waste coconut bran as raw material realizes the recycling of resources; at the same time, the method has simple process, low cost, high recovery efficiency (up to 84.36%), and has good application prospects. (4) Wide application: The obtained micro-narrow mesoporous high hydrophobicity biochar can be widely used in wastewater treatment, gas purification, oil-water separation and other fields, showing excellent adsorption performance and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Other features, objects and advantages of the present application will become more apparent by reading the detailed description of non-limiting embodiments made with reference to the following drawings:

[0021] Figure 1 It is a schematic diagram of the preparation process of the present invention;

[0022] Figure 2 a and b are the N2 adsorption-desorption isotherms and pore size distribution diagrams of BC and MTMS@BC-0.25, respectively;

[0023] Figure 3 Infrared spectra of BC and MTMS@BC-0.25;

[0024] Figure 4 XRD spectra of BC and MTMS@BC-0.25;

[0025] Figure 5 The water contact angle measurements of BC and MTMS@BC-0.25;

[0026] Figure 6 The adsorption penetration curves of L2 by BC and MTMS@BC-0.125, MTMS@BC-0.25, MTMS@BC-0.50 and MTMS@BC-1.00;

[0027] Figure 7 This is the adsorption breakthrough curve of MTMS@BC-0.25 during cyclic use. DETAILED DESCRIPTION

[0028] The present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. It is also necessary to explain that, for ease of description, only the parts related to the invention are shown in the accompanying drawings.

[0029] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0030] 1. Implementation

[0031] Example 1

[0032] (1) Raw material pretreatment: Coconut bran was selected as the raw material, and was first repeatedly washed with deionized water to remove impurities, and then dried to constant weight. The dried coconut bran was crushed and sieved through a 40-mesh sieve to obtain uniform particles with a particle size of about 0.425 mm.

[0033] (2) Phosphoric acid impregnation: The coconut husk particles obtained in step (1) were mixed with phosphoric acid in a mass ratio of 1:3, and stirred at room temperature for 0.5 h to allow the phosphoric acid to fully penetrate into the coconut husk particles. Thereafter, the mixture was transferred to an oven and dried at 110° C. for 2 h.

[0034] (3) High-temperature pyrolysis: The dried mixture in step (2) was placed in a tube furnace and subjected to high-temperature pyrolysis in a protective atmosphere with a carbon dioxide flow rate of 100 ml / min. The pyrolysis temperature was set to 800°C and maintained for 2 h, so that the coconut bran particles underwent carbonization reaction at high temperature to form biochar (BC) with a micro / narrow mesoporous structure.

[0035] (4) Surface hydrophobic modification: The BC obtained in step (3) was added to a methyltrimethoxysilane aqueous solution (mass fraction 0.25%) at a mass ratio of 1:10, and oscillated at 25°C for 12 hours to allow the methyltrimethoxysilane molecules to undergo hydrolysis and condensation reaction on the surface of the biochar and be grafted onto the surface of the biochar. Subsequently, the modified biochar was separated from the solution by filtration, and the obtained slurry was vacuum dried at 120°C for 24 hours to finally obtain a micro-narrow mesoporous highly hydrophobic biochar (MTMS@BC-0.25).

[0036] Example 2

[0037] On the basis of Example 1, the mass fraction of the methyltrimethoxysilane aqueous solution was changed to 0.125% to obtain highly hydrophobic biochar MTMS@BC-0.125.

[0038] Example 3

[0039] On the basis of Example 1, the mass fraction of the methyltrimethoxysilane aqueous solution was changed to 0.50 to obtain highly hydrophobic biochar MTMS@BC-0.50.

[0040] Example 4

[0041] On the basis of Example 1, the mass fraction of the methyltrimethoxysilane aqueous solution was changed to 1.00% to obtain highly hydrophobic biochar MTMS@BC-1.00.

[0042] 2. Characterization and Analysis of Materials

[0043] 1. Determination of pore size and specific surface area

[0044] As shown in Table 1, these are the texture property parameters of BC, MTMS@BC-0.125, MTMS@BC-0.25, MTMS@BC-0.50 and MTMS@BC-1.00.

[0045] Table 1

[0046]

[0047] 2. Infrared spectroscopy (FTIR) characterization

[0048] Combined with Figure 3 BC and MTMS@BC-0.125 show that 585cm- 1 The peaks at are related to the stretching vibration of Si–O bonds, and these peaks indicate that MTMS has been successfully grafted onto APC.

[0049] 3. X-ray diffraction characterization

[0050] Combined with Figure 4 It can be observed that the XRD spectra of BC and MTMS@BC-0.125 both show two significant broad diffraction peaks at 23.5° and 43.4°, respectively, which correspond to the (002) and (100) crystal planes of the carbon structure. The appearance of the (002) peak is mainly attributed to the stacking defects between carbon grains; the (100) peak is relatively weak, which reflects the sp2 hybrid arrangement characteristics of the graphite structure. In addition, the MTMS@BC-0.125 sample treated with MTMS coating does not show other sharp or strong diffraction peaks in the XRD spectrum, indicating that it mainly maintains the characteristics of the amorphous structure.

[0051] 4. Hydrophobicity analysis

[0052] Combination Figure 5It can be seen that after MTMS was grafted onto BC, the hydrophobicity of MTMS@BC was enhanced, showing strong hydrophobicity. Biochars with different degrees of hydrophobicity were prepared by changing the mass fraction of MTMS. It was found that with the increase of MTMS, the contact angle first increased and then decreased, which was consistent with the change trend of specific surface area.

[0053] 3. Evaluation of adsorption and desorption performance

[0054] After adsorbing L2, MTMS@BC-0.125 was treated in a 100℃ water bath for 60 min for regeneration, and then L2 was adsorbed again after regeneration. This cycle was repeated 4 times. The experimental results are shown in Figure 6 The results show that after 4 cycles of adsorption / regeneration, the regeneration rate can reach 84.36%. As can be seen from Table 2, compared with other carbon materials, the regeneration of MTMS@BC-0.125 can be achieved at a lower heating temperature and shows good cycle performance in the absence of other auxiliary agents.

[0055]

[0056] In summary, the micro / narrow mesoporous high-hydrophobic biochar produced by the present invention provides abundant adsorption sites due to its unique micro / narrow mesoporous structure, and its high hydrophobicity effectively prevents water vapor adsorption, thereby being able to further increase the adsorption amount of siloxanes and significantly improve the adsorption efficiency. The raw material used in the invention is widely available waste coconut husk. After high-temperature calcination to obtain biochar, it is treated by a simple and efficient impregnation method to obtain highly hydrophobic biochar, which not only realizes the resource utilization of waste, but also greatly simplifies the production process, so the production cost can be greatly reduced. In practical applications, the product can still maintain a siloxane adsorption capacity of up to 84.36% after a simple heating and desorption experiment (such as four adsorption and desorption cycles). This performance is significantly better than biochar modified by other methods, showing its excellent recycling potential and practical application value.

[0057] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the present application.

Claims

1. A method for preparing micro / narrow mesoporous highly hydrophobic biochar, comprising the following steps: (1) Raw material pretreatment: Coconut bran was selected as the raw material, firstly washed with deionized water to remove impurities, and then dried to constant weight; the dried coconut bran was crushed and sieved through a 40-mesh sieve to obtain uniform particles with a particle size of about 0.425 mm; (2) Phosphoric acid impregnation: The coconut husk particles obtained in step (1) are uniformly mixed with phosphoric acid, and stirred continuously at room temperature for 0.5 h to allow the phosphoric acid to fully penetrate into the coconut husk particles; then, the mixture is transferred to an oven and dried at 110° C. for 2 h; (3) High-temperature pyrolysis: The dried mixture in step (2) is placed in a tube furnace and subjected to high-temperature pyrolysis in a protective atmosphere with a carbon dioxide flow rate of 100 ml / min; the pyrolysis temperature is set to 800°C and maintained for 2 h, so that the coconut bran particles undergo carbonization reaction at high temperature to form biochar BC with a micro / narrow mesoporous structure; (4) Surface hydrophobic modification: The BC obtained in step (3) was added to a methyltrimethoxysilane aqueous solution and oscillated at 25°C for 12 h to allow the methyltrimethoxysilane molecules to undergo hydrolysis and condensation reaction on the surface of the biochar and be grafted onto the surface of the biochar; subsequently, the modified biochar was separated from the solution by filtration, and the obtained slurry was vacuum dried at 120°C for 24 h to finally obtain the micro-narrow mesoporous highly hydrophobic biochar MTMS@BC-0.

25.

2. A method for preparing micro / narrow mesoporous highly hydrophobic biochar according to claim 1, characterized in that: In the step (2), the mass ratio of coconut bran to phosphoric acid is 1:

3.

3. A method for preparing micro / narrow mesoporous highly hydrophobic biochar according to claim 1, characterized in that: In the step (4), the mass fraction of the methyltrimethoxysilane aqueous solution is 0.25%.

4. A method for preparing micro / narrow mesoporous highly hydrophobic biochar according to claim 1, characterized in that: In the step (4), the mass ratio of BC to the methyltrimethoxysilane aqueous solution is 1:10.

Citation Information

Cited By

  • Preparation method and application of super-hydrophobic modified nitrogen-phosphorus co-doped bottom mud biochar

    CN122298379A